Village Fund Budget Analysis in Support Village, Tanjung District, North Lombok Regency - Baiq Karlida Miftahul Jannah (Formosa Journal of Multidisciplinary Research, 2023)
This study aims to analyze the realization of the village fund budget in Sokong Village, Tanjung District, North Lombok Regency for 4 years from 2018 to 2021 using a value for money approach with an analysis consisting of economic ratios, efficiency ratios, and effectiveness ratios. The results of this study indicate that in terms of economic ratios, Desa Sukong gets the economic category, which means that there is no waste when obtaining resources. In terms of efficiency, the government of the Village of Support has obtained the efficient category, which means that the Government of the Village of Support has been able to use as few resources as possible. In terms of effectiveness, the government of the Village of Support is in the category of quite effective, which means that the Government of the Village of Support is not wise enough in using the budget or the resulting output has not been able to meet the expected goals.